Modelling of material recovery from waste incineration bottom ash. (15th March 2020) - Huber, Florian
Highlights: Five plants for treatment of waste incineration bottom ash were modelled. Material flow analysis based on literature data and previous studies was applied. Crushers improve metal recovery and ageing decreases mass of recoverable metals. Magnetic scrap is contaminated by Cd (up to 114 mg/kg) and Cu (up to 9, 900 mg/kg). Composition of mineral material depends mostly on mass of separated metals. Abstract: Bottom ash from municipal solid waste incineration is usually treated in order to recover valuable materials like metals and to generate a mineral material for utilisation in construction industry or disposal. At present, different technologies and combinations thereof are used for bottom ash treatment resulting in different quantities and qualities of the final products (metals and minerals). So far, a comparison of these technologies is hardly possible based on the available literature. Hence, the present paper presents and applies a modelling approach that allows predicting the quantities and qualities (in terms of composition) of the final outputs of bottom ash treatment plants. In particular, material flow analysis models of five different bottom ash treatment plants were established on goods, material and element level and the mass and composition of the output flows of these plants were calculated based on an input of 118, 000 Mg/a of bottom ash dry matter. The highest recovery of metals (up to 8640 ± 820 Mg/a iron, 1530 ± 220 Mg/a aluminium, 627 ± 73 Mg/a stainless steel and 608 ± 70 Mg/a heavy non-ferrous metals) can be achieved in plants that apply comminution before any ageing processes and are equipped with jiggers, inductive sorting systems and/or a high number of eddy current separators. The iron scrap fractions separated from bottom ash are contaminated by up to 114 ± 44 mg/kg Cd and up to 9900 ± 3300 mg/kg Cu, which might impair their suitability for recycling. Only minor differences in the composition of mineral material generated by different treatment plants could be observed.